Synthesis and characterization of mesoporous TiO2 nanostructured films prepared by a modified sol-gel method for application in dye solar cells - Muniz, E. C. [UNESP]; Goes, M. S. [UNESP]; Silva, J. J. [UNESP]; Varela, José Arana [UNESP]; Joanni, E.; Parra, R.; Bueno, Paulo Roberto [UNESP] (Elsevier B.V., 2011)
Anatase TiO2 colloidal dispersions were obtained by hydrothermal synthesis at 200 degrees C from titanium isopropoxide gels modified with acetic acid in the presence of a non-ionic surfactant. Absolute ethanol, anhydrous terpineol and ethyl cellulose were added to this anatase dispersion resulting in a 23 wt% TiO2 paste. Mesoporous films for application as working electrodes in dye-sensitized solar cells were prepared by the screen-printing method, yielding reproducible films with thicknesses about 10 mu m and desired porosity levels in a single printing operation. An average energy conversion efficiency of 5.2%, and a fill factor of 0.66 were achieved with anatase particle sizes ranging between 15 and 20 nm. The reproducibility of the results was confirmed by electrochemical impedance spectroscopy analysis. (c) 2010 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Nanoparticle TiO2; Sol-gel; Hydrothermal synthesis; DSC